Basic pediatric intensive care course (BPICC) India - A success storyxs - Madhumati Otiv (Wolters Kluwer Medknow Publications, 2014)
Basic pediatric intensive care course (BPICC) is a joint initiative of Pediatric Intensive Care Chapter (IAP) and the Indian Society of Critical Care Medicine, (ISCCM-Pediatrics section). This two day course was started in Critcare Conference 2009-Agra by the founder conveners Dr Praveen khilnani, Dr Rajiv Uttam and Dr Krishan Chugh. Currently more than 25 courses have been administered nation wide and more than 50 national wide instructors are teaching these courses. As the demand for this course has grown exponentially in past 4 years this additional conveners have been added on to the BPICC team as regional leaders. This addition will surely bring about efficient and effective dissemination and nationwide promotion. Following intensivists have agreed to shoulder the responsibility of being additional conveners.